2019
DOI: 10.1155/2019/2018598
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Specific Reference Intervals for Myocardial Enzyme Activity in Healthy Chinese Han Population Aged 1∼<18 years

Abstract: Age-and sex-specific reference intervals (RIs) for myocardial enzyme activity of children and adolescents are not available in China. Our study aimed to establish age-and gender-related RIs for AST, LDH, CK, and CKMB activity in healthy Chinese Han population aged 1∼<18 years. Healthy Han children and adolescents (n � 6322, 1∼<18 years old) were assessed from completed questionnaires and defined criteria from communities and schools in 5 administrative districts of Jilin Province from September 2017 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In fact, our research group has conducted some studies in the early stage, and the results confirm that age, sex, and statistical methods have a certain influence on the reference interval. 3 , 4 Therefore, establishing accurate RIs for local laboratories is one of the most important factors for clinical diagnosis.…”
mentioning
confidence: 99%
“…In fact, our research group has conducted some studies in the early stage, and the results confirm that age, sex, and statistical methods have a certain influence on the reference interval. 3 , 4 Therefore, establishing accurate RIs for local laboratories is one of the most important factors for clinical diagnosis.…”
mentioning
confidence: 99%
“…Previous research has found that the differences in RIs of analytes are due to their complex patterns of biological sources of variations, such as region, race, diet, and more individual characteristic [1,2]. Data from the studies we have published con rms that establishing age-and sexappropriate local RIs is more accurate and reliable for providing clinical decision support, especially in pediatrics [3][4][5][6].…”
Section: Introductionmentioning
confidence: 86%
“…The samples were transported to the laboratory and centrifuged at 1200 ×g for 10 min within 1 h after collection. Specimens that were icteric, hemolyzed, or lipemic were removed prior to analysis, and then the activity or concentration of 26 biochemical analytes were determined on the VITROS 5600 Integrated Quali ed laboratory pro ciency and staff training were described in the research conducted in the same period [3,4]. Analytical procedures were performed according to the manufacturer's instructions and laboratory protocols, including regular maintenance, function checks, calibration, and internal quality control.…”
Section: Sample Collection and Laboratory Proceduresmentioning
confidence: 99%
“…3 Biochemical reference intervals in comparison with other studies. [ 1 ] represents the current study, [ 2 ] represents kit insert (F for female, M for male), [ 3 ] represents Choi et al, [ 4 ] represents Zhao et al, [ 5 ] represents Liu et al, [ 6 ] represents Higgins et al …”
Section: Resultsmentioning
confidence: 99%
“…Data from several studies suggest that age-and sex-specific RIs are more reliable to provide clinical decision support in the pediatric population [3][4][5]. Moreover, differences in analytical systems and statistical procedures may result in the differences between RIs reported in different studies [6][7][8][9]. Every aspect should be considered during the determination of accurate RIs.…”
Section: Introductionmentioning
confidence: 99%